Behavior during cyberbullying episodes: Initial validation of a new self‐report scale. Issue 1 (28th January 2019) - Pozzoli, Tiziana; Gini, Gianluca
Abstract : Research on cyberbullying has been growing worldwide, with much of the focus on the characteristics of perpetrators and targets of cyberbullying. In recent years, increasing attention has been paid on bystanders of cyber‐attacks. This study presents the Italian validation of a newly developed self‐report scale that measures different forms of participation in cyberbullying, namely cyberbullying, cybervictimization, cyber‐defending and cyber‐passive bystanding. We used responses from 561 young adolescents (289 girls; mean age = 12 years, 1 month; SD  = 9 months) attending middle schools in Italy. A 16‐item scale was developed paralleling the content of an already existing scale that measures young adolescents' behavior in traditional bullying. Confirmatory factor analysis supported the four‐dimensional structure of the scale and the four subscale's scores showed acceptable levels of internal consistency. Multigroup analyses demonstrated full scalar invariance of the scale across gender groups. Finally, each behavior in the electronic context was positively correlated with its counterpart in the school context, suggesting certain stability across contexts. It is concluded that the scale may be a first, promising attempt to measure different youths' behavior during cyberbullying episodes.